Safety of buccal infiltration local anaesthesia for dental procedures. Issue 2 (28th February 2019) - Dougall, Alison; Apperley, Olivia; Smith, Gillian; Madden, Louise; Parkinson, Laura; Daly, Blanaid
Abstract : Aim: To assess the safety of buccal infiltration local anaesthetic (LA) without additional factor replacement in patients with haemophilia (PWH) and association with clinical experience of the operator. Methods: A consecutive sample of participants with mild, moderate and severe haemophilia scheduled to have dental treatment were recruited from a comprehensive care centre in Ireland. Infiltration LA was administered using a standard technique. Safety was defined as any adverse event at time of administration, immediate postoperative, or postoperative period. Clinical experience was dichotomized into fewer or greater than three years clinical experience. Results: N = 135 buccal infiltration LAs without additional factor replacement were provided to N = 71 participants with mild (n = 20; 28%) and moderate to severe haemophilia (n = 51; 72%). Successful local anaesthesia was achieved in n = 133 cases (99%). No (0%) adverse bleeding events were recorded for any participants at time of administration of LA or during follow‐up. Three out of 135 (2.2%) LAs recorded superficial bleeding 30 seconds after administration of LA, all of which resolved within 2 minutes with application of pressure; 4 out of 135 (3%) LAs produced a superficial haematoma at the site of injection no greater than 2 mm all of which resolved at 4 minutes. There were no differences in bleeding rates between clinicians by level of experience ( P = 0.435) or by severity of bleeding disorder ( P = 1.0). Conclusion: Local anaesthetic is safe to administer via buccal infiltration for people with mild, moderate and severe haemophilia without additional factor cover. This finding holds true regardless of operator experience.